Determination of Some Agronomic and Fruit Quality Characteristics of Some Watermelon Accessions from Turkish Watermelon Germplasm - Ercüment Atlı; İlknur Solmaz; Nebahat Sarı; Haşim Kelebek (Turkish Journal of Agriculture: Food Science and Technology)
This study has been conducted to determine the fruit quality parameters such as sugar and carotenoid content as well as plant and fruit characteristics of 11 local watermelon genotypes from watermelon genetic resources collection of Cukurova University, Department of Horticulture. First and 50% male and female flowering period, main stem length, main stem diameter, number of nodes on main stem, total yield, fruit weight, fruit length, fruit diameter, fruit rind thickness, total soluble solids (TSS), sugar and carotenoid contents were examined. Although there is no significant difference for main stem diameter and number of nodes on the main stem, significant differences were obtained for total yield, sugar and carotenoid composition of the genotypes. Carotenoid and sugar analysis were performed with a high-performance liquid chromatographic method coupled with diode-array detector (HPLC-DAD) and HPLC coupled with refractive index detector (RID), respectively. In all studied genotypes, cis-13-lycopene and β-carotene were the most abundant compounds. As expected for watermelon genotypes, the main sugar found in all studied genotypes was fructose. According to PCA analyses, genotypes were characterized by physical and chemical composition. Overall evaluation of results revealed that Kar 147 had better potential with carotenoid, sugar contents and fruit characteristics.